HERSK-TNA, Hekla Real-Time Seismic Network - Transnational Access Eurovolc project - Möllhoff, Martin; Bean, Christopher J.; Vogfjörd, Kristin S. (GFZ Data Services, 2021)
Abstract Hekla is one of the most active and dangerous volcanoes in Iceland presenting a high hazard to air travel and a growing tourist population. It is hence important to monitor its seismic activity in real-time. However, until now the pre-eruption warning time is only around one hour. A temporary seismic network deployed by us around Hekla summit in 2012 recorded unexpected background micro-seismicity (Eibl et al., 2014). Seismic monitoring directly on the edifice could provide a possible means to early-warning if micro-seismicity on Hekla increases prior to an eruption. In addition, the monitoring of a fissure eruption close up is expected to better understand how it initiates in detail. This prompted the installation of the Hekla Real-Time Seismic Network (HERSK) in 2018 (Möllhoff et al., 2018a/b). We experienced logistical difficulties especially in winter months, mainly in relation to power provision. In this project we build on the first phase of HERSK to (1) test novel ways of powering stations that transmit real-time data in very harsh environments and (2) to work towards a real-time event detection and location system dedicated to seismic activity at Hekla volcano. The development of the real-time system necessitates the derivation of a velocity model which we derive by inverting observed microseismicty data. This opens the way to image the internal structure of Hekla volcano. Waveform data are available from the GEOFON data centre, under network code XE.